Stylistic Devices in The Schoole of Vertue, an Early Modern Manual of Good Conduct for Children - Rutkowska, Hanna (Studia Anglica Posnaniensia, 2016)
This paper is a case study examining the choice and interaction of stylistic devices employed in The Schoole of Vertue, Francis Segar and Robert Crowley’s manual of good manners for children issued between 1582 and 1687. It was designed to convince its readers that particular patterns of behaviour were socially beneficial and worth following. In order to enhance the attractiveness, persuasiveness, and mnemonic qualities of the text, several stylistic devices are employed in the manual, including, for example, rhymes, acronyms, as well as binomials. It is generally agreed that repetitive patterns (especially binomials) are typical of formal registers, and particularly plentiful in legal and literary texts in Early Modern English, but the present study shows that similar rhetorical devices were also readily employed in the less formal and elevated style of manuals of good behaviour. Another rhetorical device frequently used in the manual under consideration consists in addressing the reader directly with the second person singular pronoun, especially in imperative constructions, thus creating an ambiance of emotional closeness, characterising the relationship between the master and the pupil.